The Effect Of Preoperative Gabapentin on Pain Severity After Posterior Urethral Surgery: A Randomized, Double-Blind, Placebo-Controlled Study - ghiasy, saleh; Tayebi-azar, Ali; Alinezhad, Amin; Fallah-karkan, Morteza; Salimi, Hojat; Hojjati, Seyyed Ali; Hosseini, Jalil (Urology Journal, 2020)
Purpose: Prevention and treatment of urethroplastic postoperative pain is a major challenge in post-surgery care. gabapentin can treat postoperative pain by preventing excessive sensitivity to the central nervous system. we have tried to compare the effect of gabapentin with the placebo on reducing the pain associated with posterior urethroplasty in patients. Material and Method: This prospective, randomized, double-blind study was scheduled in Shohad e Tajrish hospital where a single dose of Gabapentin was compared with placebo given to patients preoperatively. In this study,100 patients with posterior urethral stricture were included for surgery with 50 patients in each arms .All patients underwent posterior urethroplasty. After surgery, the pain level is assessed and evaluated by the visual analog scale in two hours,four hours, six hours,eight hours, twelve hours, and 24 hours after the operation. Result: In this study, there was a significant difference in the pain level that was evaluated by the visual analog scale in two hours, four hours, six hours, eight hours, twelve hours, and 24 hours after the surgery (p.value <0.001). We also found a significant decrease in morphine consumption in the gabapentin group vs the placebo group. (p.value <0.001) The post-surgery assessments showed significant lower adverse effects such as vomiting, nausea, drowsiness, and pruritus in the gabapentin group vs. placebo group. Conclusion: The consequences of this study revealed that gabapentin effective in controlling posterior urethroplasty postoperative pain, consumption of opioid, nausea, vomiting, drowsiness, and pruritus compared with the placebo group.